Characterization of flameless combustion of natural gas in laboratory scale furnace - Abuelnuor, Abuelnuor (2013)
In this work, the operational and emission of the laboratory scale burner under the flameless combustion regime using natural gas as a fuel is examined. In the present setup, the combustor is equipped with parallel jet burner systems with controlled gas fuel and oxidizer. The combustor consists of several ports that are used to measure temperature variation and analyze gas emission. The atmospheric air was heated by flowing it inside the chamber until the air temperature increased to approximately the auto ignition temperature of the fuel. It is observed that, flameless combustion can be obtained using natural gas as a fuel. The value of NOX emission during flameless combustion was reduced of about 70% in average compared to the conventional flame for the different equivalence ratio. Additional work shows that the equivalence ratio on flameless combustion has little effect of NOX emissions in this study.